Cultural contact and appropriation in the Axial-Age Mediterranean world : a periplos - Halpern, Baruch.; Sacks, Kenneth.; Kelley, Tyler Edward. (Culture and History of the Ancient Near East, 2017)
Karl Jaspers dubbed the period, 800-400 BCE, the Axial Age. Axial it was, for out of it emerged the idea of Greek culture, with its influence on Roman and later empires. Jaspers' Axial Age was the chrysalis of culturally-meaningful modernity. Trade expands intellectual horizons. The economic and political effects permeate such social domains as technology, language and worldview. In the last category, many issues take on an emotional freight - the birth of science, monotheism, philosophy, even theory itself. Cultural Contact and Appropriation in the Axial-Age Mediterranean World: A Periplos , explores adaptation, resistance and reciprocity in Axial-Age Mediterranean exchange (ca. 800-300 BCE). Some essayists expand on an international discussion about myth, to which even the Church Fathers contributed. Others explore questions of how vocabulary is reapplied, or how the alphabet is reapplied, in a new environment. Detailed cases ground participants' capacity to illustrate both the variety of the disciplinary integuments in which we now speak, one with the other, across disciplines, and the sheer complexity of constructing a workable programme for true collaboration.